What should a (neuro) logopaedic therapist know about feeding the youngest patients (0-3) with feeding disorders. Part i. Feeding (nutrition) – meaning, types, functions - Marciniak-Firadza, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
Food intake is an essential element to maintain homeostasis of the body, and the way of feeding. Whereas the type of feeding in the neonatal and infancy stages influence on one side the health of children and teenagers, and next adults, and on the other side, the way of feeding newborns, infants and toddlers has great impact on the development of the orofacial area being a biomechanical base of articulation. Feeding is also a basic environmental factor having crucial influence on the development of a child’s brain. Not providing the child with all of the necessary elements and energetic needs in the prenatal stage and on the further stages of development, especially in infancy, can have a negative effect on the brain’s structural development (e.g., insufficient myelination of neurons), as well as interfere with its functions, for example, in terms of neurotransmitters. In this article, I will undertake selected aspects of feeding disorders understood as both giving food and providing food, as well as feeding the offspring with their own milk.